2000
DOI: 10.1152/ajplung.2000.279.1.l143
|View full text |Cite
|
Sign up to set email alerts
|

Abrogation of bleomycin-induced epithelial apoptosis and lung fibrosis by captopril or by a caspase inhibitor

Abstract: Angiotensin-converting enzyme is involved in apoptosis of alveolar epithelial cells (Wang R, Zagariya A, Ang E, Ibarra-Sunga O, and Uhal BD. Am J Physiol Lung Cell Mol Physiol 277: L1245-L1250, 1999). This study tested the ability of the angiotensin-converting enzyme inhibitor captopril or the caspase inhibitor Z-Val-Ala-Asp-fluoromethylketone (ZVAD-fmk) to block alveolar epithelial cell apoptosis and lung fibrosis in vivo in response to bleomycin (Bleo). Male Wistar rats received 8 U/kg of Bleo (bleomycin sul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
194
0
4

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(207 citation statements)
references
References 24 publications
9
194
0
4
Order By: Relevance
“…Apoptosis of pulmonary endothelial and epithelial cell plays an important role in the initiation and progression of pulmonary fibrosis (2,9,11,32), and the mechanism of bleomycininduced apoptosis in lung cells has been a critical topic for pulmonary fibrosis research (17,18,28,30). The major finding of this study is that, in primary pulmonary endothelial cells, bleomycin induces early activation of the extrinsic apoptotic pathway, but not of the intrinsic apoptotic pathway.…”
Section: Discussionmentioning
confidence: 77%
“…Apoptosis of pulmonary endothelial and epithelial cell plays an important role in the initiation and progression of pulmonary fibrosis (2,9,11,32), and the mechanism of bleomycininduced apoptosis in lung cells has been a critical topic for pulmonary fibrosis research (17,18,28,30). The major finding of this study is that, in primary pulmonary endothelial cells, bleomycin induces early activation of the extrinsic apoptotic pathway, but not of the intrinsic apoptotic pathway.…”
Section: Discussionmentioning
confidence: 77%
“…We demonstrated that Elovl6 deficiency resulted in exacerbation of pulmonary fibrosis in mice when they are exposed to BLM. A number of evidence established that BLM induced apoptosis in the alveolar epithelial and endothelial cells [25][26][27] , which has a key role in the initiation and progression of pulmonary fibrosis 28 . Indeed, we found the induction of apoptosis and caspase 3 activation in the lung from Elovl6 À / À mice, and confirmed them in Elovl6-kockdown LA-4 cells.…”
Section: Blm Treatment Decreases Elovl6 Expression In the Lungmentioning
confidence: 99%
“…37 Blockade of apoptosis by either the angiotensin-converting enzyme (ACE) inhibitor captopril, caspase inhibition or the forced expression of p21 in lung epithelial cells exerted antifibrotic effects in animal models. 36,38,39 Together, these data suggested that the fibrotic response is secondary to the apoptotic death of epithelial cells in the lung. The death receptor Fas was found to be expressed in AECs within the lungs of IPF patients and circulating levels of its ligand FasL correlated with disease activity.…”
mentioning
confidence: 86%
“…Apoptosis of alveolar epithelial cells (AECs) is found in patients with idiopathic PF (IPF) and in animal models of the disease. [34][35][36] The epithelial apoptosis colocalizes with myofibroblasts where collagen deposition is severe. 37 Blockade of apoptosis by either the angiotensin-converting enzyme (ACE) inhibitor captopril, caspase inhibition or the forced expression of p21 in lung epithelial cells exerted antifibrotic effects in animal models.…”
mentioning
confidence: 99%